Response of Different Doses of NPK and Boron on Growth and Yield of Broccoli (Brassica oleracea L. var. italica) - Singh, Manoj Kumar; Chand, Trilok; Kumar, Mukesh; Singh, K. V.; Lodhi, S. K.; Singh, V. P; Singh Sirohi, Vikrant (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was carried out to examine the optimum doses of NPK and boron application on broccoli in irrigated agro-ecosystem of western Uttar Pradesh during rabi 2009-10 and 2010-11. Seven different treatments including control were used in Randomized Block design (RBD). The results revealed significant response on growth and yield of broccoli for different treatments. Application of 120 kg N+60 kg P2O5+40 kg K2O+15 kg B ha-1 gave maximum plant height plant-1 (65.33 cm), number of leaves plant-1 (18.26), length longest leaf (52.99 cm), width of longest leaf (17.98 cm), spread of plant (55.53 cm) and stem diameter (4.47 cm), whereas in control was minimum pronounced plant height plant-1 (58.66 cm), number of leaves plant-1 (12.33), length longest leaf (42.70 cm) width of longest leaf (14.18 cm), spread of plant and stem diameter (3.04 cm). Similar, pattern on the curd diameter (13.69 cm), length of curd (16.33 cm), weight of curd plant-1 (286.89 g), weight of sprout plant-1 (126.89 g), weight of curd and sprout plant-1 (0.390 kg) and total yield Curd+sprout (148.51 q ha-1) was recorded with the application of 120 kg N+60 kg P2O5+40 kg K2O+15 kg B ha-1’ and minimum was under control treatment.